Doppler‐Guided Acoustically Active Injection Catheter: Transendocardial Delivery Assessed by an Efficacy Testing Animal Model. (3rd May 2021) - Katayama, Minako; Gades, Naomi M.; Singh, Vijay P.; Devick, Katrina L.; Zarbatany, David; Vaitkus, Veronica V.; Belohlavek, David L.; Fortuin, F. David; Belohlavek, Marek
Abstract : Percutaneous transendocardial injections of therapeutic agents into the myocardium may not always be effective. We used an animal model for assessing the efficacy of the injections using linoleic acid as a testing agent. Efficacious delivery into the myocardium of a beating heart was indicated by rapidly developed local myocardial necrosis and wall motion abnormalities using echocardiography. We employed this experimental model to test our innovative technology, an acoustically active injection catheter. The Doppler ultrasound‐guided acoustically active injection catheter effectively delivers the substance to the myocardium but needs further technical improvements to minimize an unwanted systemic distribution of the agent.